The art of the board : fun & fancy snack boards, recipes & ideas for entertaining all year - Carney, Olivia (Gibbs Smith, 2022)
"Charcuterie and snack board influencer, Olivia Carney (That Charcuterie Chick)'s The Art of the Board features 75 fun and fancy seasonally inspired snack boards and recipes, and is packed with step-by-step how-tos, handy tips, and festive ideas to help even the most hopeless host elevate their entertaining all year long. Not sure where to start? No problem! The in-depth introduction will walk you through all the important facts when it comes to equipment and ingredients, and the Hopeless Hostess Appendix covers everything from Board Care 101, to finding the perfect board to match every mood and vibe, to step-by-step explanations and photographs that show how to bring your meat-, cheese-, and tablescape-presentation skills to the next level. There's even helpful suggestions make your cheese plates travel-friendly so you never arrive empty-handed. Each board is labeled with difficulty level, approximate cost, and dietary accommodations, so you'll always find a showstopper to fit your lifestyle and budget. With That Charcuterie Chick's friendly guidance, you'll go from hopeless host to host with the most-one salami rose at a time"--